The Relationship between Values, Norms, and Morals in Forming National Character Through Social Studies Education - Selsha Juliana Dwi Putri; Hotimah, Ulin Khusnul; Noviyanti, Silvina; Chan, Faizal (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
The goal is to understand how these elements work together to foster a strong ethical and moral foundation in students. Using a qualitative literature review method, this study analyzes academic findings to explore how values serve as life principles, norms provide a framework for behavior, and morals guide ethical decisions. The findings emphasize that social studies education is a strategic platform for integrating values, norms, and morals, enabling students to develop critical thinking, empathy, and social responsibility. By embedding these elements into the curriculum, students are equipped to face real-life challenges with integrity and adaptability. The study concludes that a holistic approach, integrating these three elements, is essential to building strong national character. Furthermore, the study identifies the need for contextual and active learning strategies, such as problem-based learning, to enhance the application and relevance of these concepts in the classroom environment. The novelty of this study lies in its comprehensive framework, which moves beyond traditional character education by emphasizing the dynamic interactions between values, norms, and morals. This approach provides a new perspective on social studies education as a transformative tool for building character. Future research is recommended to include empirical data through classroom experiments or case studies to validate the framework, ensure its effectiveness in real-world educational settings and further strengthen its practical implications.